Storytelling and ecology empathy, enchantment and emergence in the use of oral narratives - Nanson, Anthony (Bloomsbury advances in ecolinguistics, 2023)
"Linking the ongoing ecological crisis with contemporary conditions of alienation and disenchantment in modern society, this book investigates the capacity of oral storytelling to reconnect people to the natural world and enchant and renew their experience of nature, place and their own existence in the world. Anthony Nanson offers an in-depth examination of how a diverse ecosystem of oral stories and the dynamics of storytelling as an activity can catalyse different kinds of conversation and motivation, helping us resist the discourse of powerful vested interests. Detailed analysis of traditional, true-life and fictional stories shows how spoken narrative language can imbue landscapes, creatures and experiences with enchantment and mediate between the inner world of consciousness and outer world of ecology and community. A pioneering ecolinguistic and ecocritical study of oral storytelling in the modern world, Storytelling and Ecology offers insight into the ways that sharing stories in each other's embodied presence can open up spaces for transformation in our relationships with the ecological world around us"--Provided by publisher.